Sociodemographic and behavioral characterization of men with infection by the human immunodeficiency virus. Health Area I. Cienfuegos Municipality. 2014 - Katiuska Díaz Quintero; María Lina Valdés Gómez; Leticia Castro Morejón; Julio César Díaz Marrero; José Aurelio Díaz Quiñones; Esther Yarinely Hernández Dieguez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2018)
Foundation: The main struggle against the human immunodeficiency virus is prevention, fro that it is necessary to take into consideration the most vulnerable groups and the associated risk factors. Objective: to characterize men infected by human immunodeficiency socio-demographically and behaviorally. Method: Men case and control study from Health Area I, Cienfuegos Municipality. The population was described according to socio-demographic and behavioral variables selected and the differences between cases and controls were set according to these variables. The cases were diagnosed with human immunodeficiency virus, from 1986 to 2013, information obtained in the Department of Epidemiology of this area; the 56 controls were paired by the same age of cases and were selected two from each one. A survey was applied to both groups. The Squared-Ji was used to identify the association for estimating the risks it was used the Odds ratio; A level of significance was set at 0.05. Results: The main factors identified were the marital link or consensual relation, not using condoms, antecedents of sexually transmitted infections, having sex with other men, transactional sex, and the visit to places of meeting. Conclusion: The identified risk factors, behavioral ones with strongest presence, denote that there is still lack of risk perception. For this reason, it is necessary to provide more information to people that allow them building knowledge to have a healthy sexual life.